Percutaneous unilateral biportal endoscopic discectomy for symptomatic lumbar disc herniation in geriatric patients - Qin, Rongqing; Guan, Anhong; Zhu, Min; Zhou, Pin; Zhou, Bing; Zhou, Ruihua; Guan, Zaiyong (Frontiers in Surgery, 2025)
PurposeThe purpose of this study is to investigate the surgical efficacy and safety of percutaneous unilateral biportal endoscopic discectomy (UBED) for symptomatic lumbar disc herniation (LDH) in geriatric patients.MethodsSeventy-two geriatric patients, aged 65–86 years (mean age: 73.2 years), with single or two-level LDH who underwent UBED from January 2020 to September 2022 were retrospectively analyzed. Clinical outcomes were evaluated based on operation time, total blood loss, hospital stay, visual analog scale (VAS) scores for leg pain, Oswestry disability index (ODI) scores, modified MacNab criteria, and postoperative magnetic resonance imaging findings.ResultsSurgery was successfully performed on all geriatric patients, with a mean operation time of 46 min (range: 32–68 min). All patients were followed up for an average duration of 14.2 ± 1.9 months (range: 12–16 months). The leg pain VAS score decreased from 8.37 ± 1.21 preoperatively to 2.03 ± 0.61 immediately after surgery, 1.56 ± 0.32 at 1 month postoperatively, 1.16 ± 0.45 at 6 months postoperatively, and 0.91 ± 0.26 at 12 months postoperatively. Similarly, the ODI score also decreased from 61.21 ± 11.06 preoperatively to 27.52 ± 10.41 immediately after surgery, 19.12 ± 7.05 at 1 month postoperatively, 12.17 ± 5.21 at 6 months postoperatively, and 8.56 ± 4.32 at 12 months postoperatively. Statistically significant differences were observed in both VAS and ODI scores at each follow-up time point when compared with preoperative parameters (P < 0.01). Also, there were 53 excellent cases, 12 good cases, and 7 fair cases based on the modified MacNab criteria at 12 months postoperatively, resulting in an excellent and good rate of 90.2%. Only three cases were found to be complicated by low extremity numbness, all of which were recovered via conservative treatment in 3 weeks. No infections or iatrogenic neurological deficits occurred in all patients.ConclusionsWe concluded that UBED achieved satisfactory results and provided a minimally invasive, effective, and safe alternative for the treatment of symptomatic LDH in geriatric patients.